Ant algorithm for flow assignment in connection-oriented networks - Walkowiak, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
This work introduces ANB (Ant Algorithm for Non-Bifurcated Flows), a novel approach to capacitated static optimization of flows in connection-oriented computer networks. The problem considered arises naturally from several optimization problems that have recently received significant attention.
Keywords: ant algorithms; flow assignment; computer networks